2015
DOI: 10.1007/s11046-015-9911-4
|View full text |Cite
|
Sign up to set email alerts
|

Scedosporium apiospermum Otitis Complicated by a Temporomandibular Arthritis: A Case Report and Mini-Review

Abstract: Scedosporium apiospermum is an ubiquitous fungus responsible for various infections in immunocompromised and immunocompetent patients. Ear infections are infrequent. We report an exceptional case of S. apiospermum external otitis complicated by temporomandibular joint arthritis. After 6 months of antibiotherapy, diagnosis was established by mycological analysis of external auditory canal and infratemporal fossae needle sampling. A satisfactory outcome was obtained after 2 months of voriconazole alone. We have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Previous published cases of MOE have involved patients suffering from HIV 4. Excluding MOE, S. apiospermum has been isolated as a cause of otitis externa in other case reports and case series;5–8 one case of otitis externa was treated solely with Voriconazole after 6 months of failed antibiotic therapy5 similar to this case; however, there was no evidence of MOE.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Previous published cases of MOE have involved patients suffering from HIV 4. Excluding MOE, S. apiospermum has been isolated as a cause of otitis externa in other case reports and case series;5–8 one case of otitis externa was treated solely with Voriconazole after 6 months of failed antibiotic therapy5 similar to this case; however, there was no evidence of MOE.…”
Section: Discussionsupporting
confidence: 55%
“…It would be wrong to ascertain from this case that all patients with a diagnosis of MOE should take antifungal medication and antibiotics; however, this case suggests that it should always be a consideration in individuals not responding to broad-spectrum intravenous antibiotic administration that the causative pathogen could be fungal. Tissue sampling has been shown to be effective in isolating pathogens when initial pus swabs have been sterile;2 as was the case with this individual, the causative pathogen was identified via extended culture of sequestered bone from the external auditory canal, and this has also been the situation in refractory cases of otitis externa 5…”
Section: Discussionmentioning
confidence: 93%
“…Scedosporium apiospermum is one of hyaline filamentous fungi that are ubiquitously present in soil, sewage and polluted water [ 25 ]. While it was previously considered to be the asexual state of Pseudallescheria boydii , it has now been shown to be two distinct species [ 27 29 ]. Presently, Scedosporium apiospermum is considered to be a species complex that is comprised of Scedosporium apiospermum sensu stricto, Scedosporium boydii , Scedosporium dehoogii , Scedosporium aurantiacum and Scedosporium minutisporum [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…While it was previously considered to be the asexual state of Pseudallescheria boydii , it has now been shown to be two distinct species [ 27 29 ]. Presently, Scedosporium apiospermum is considered to be a species complex that is comprised of Scedosporium apiospermum sensu stricto, Scedosporium boydii , Scedosporium dehoogii , Scedosporium aurantiacum and Scedosporium minutisporum [ 27 ]. The fungal isolate in the current study was definitively identified as Scedosporium apiospermum sensu stricto through the use of DNA sequencing of the β-tubulin gene, which is currently the most reliable identification method for this genus [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, although local and systemic voriconazole treatment started after admission to our hospital, the intravitreal injection was not performed, hence the optimal intraocular penetration concentration failed to achieve, or the vitreous body was not removed in time led to the poor prognosis. In a review of 15 cases associated with S. apiospermum infection, treatments with amphotericin B and ketoconazole were associated with poor prognosis, whereas voriconazole and itraconazole were associated with better prognosis [ 10 ]. In the cases we listed, voriconazole was used in nine cases, including our case, which resulted in two deaths (22%) and an improvement of seven cases (78%).…”
Section: Discussionmentioning
confidence: 99%